Building Strategic Feasibility of Higher Education through Quality Assurance - Khardi, Syarifuddin; Zoztafia, Zoztafia; Dedi Irama, Silalahi (Tarbawi, 2020)
Quality assurance in Higher Education is based on the accomplishment of the community needs in the digital era, so that demands and expects higher education to make innovations that needed by the community, such innovations are strategic higher education to provide hope to the community. The purpose of writing this article is to provide strengthening and knowledge in higher education to always determine the direction and policies that can do competition. This study is descriptive non-experimental which is an exposure to a concept of ideas supported by the literature. Based on the explanation, it was concluded that to build the strategic feasibility of higher education, quality assurance is needed that can build competitive innovations, namely creating professional Human Resources.